Effects of m-Health interventions on physical activity level and sedentary behavior in pre-hypertensive and hypertensive individuals: a systematic review (Research, Society and Development, 2022)
This study aims to identify the effects of m-Health interventions on physical activity (PA) level and sedentary behavior (SB) in pre-hypertensive and hypertensive adults. Therefore, a systematic literature search was conducted according to the guidelines defined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), in the scientific databases Web Of Science, MEDLINE/PubMed, SciELO, Scopus, and ACM Digital Library. Eligibility criteria were: clinical trials; description of the functionalities of m-Health apps (reminders, goals, wearables); description of the intervention characteristics (i.e., duration, expertise of professionals involved in the supervision, and others) and blood pressure assessment. In the end, 1447 studies were identified, of which 147 were duplicates. Through the screening by titles and abstracts, 43 studies were classified as relevant. However, only 12 studies met the eligibility criteria and were included in this systematic review. Most studies presented favorable results with the use of m-Health apps to increase PA and reduce SB. In addition, increasing PA and reducing SB might be an important non-pharmacological therapy to decrease blood pressure in  hypertensive patients, when they follow the minimum recommendations proposed by the PA guidelines of the World Health Organization (WHO). However, further studies are still needed to assess the relationship between SB, PA and the use of m-Health interventions.